Studi Komparatif Morfologi dan Tingkah Laku Leopard Gecko (Eublepharis macularius) di Penangkaran Gecko World, Kabupaten Tulungagung - Andrean Prianca Zeva Nanda; Azizatul Asyifa; Dea Putri Amalia; Diah Ayu Ningtyas; Farida Aulia Nur; Seftiana Dwi Kairunnisa; Desi Kartikasari (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2026)
This study was motivated by the growing popularity of keeping Leopard Geckos (Eublepharis macularius) with various morphs, while comprehensive information on the relationship between their physical variations and behavioral characteristics in local breeding facilities remains limited. The study aimed to identify different Leopard Gecko morphs and compare their morphological and behavioral characteristics at the Gecko World breeding facility in Tulungagung Regency. Using a descriptive qualitative approach, data were collected through direct observation of physical characteristics and behavior, interviews with the breeder, and a literature review. The results showed clear morphological differences among the three morphs, particularly in skin coloration and pattern, skin texture, and body length. Behavioral differences were also observed, with certain morphs exhibiting varying levels of aggressiveness and different responses to environmental stimuli. Overall, the findings indicate that the physical characteristics of Leopard Geckos influence how they interact with and adapt to their captive environment. For example, they adjust to higher ambient temperatures by changing their skin color and close their eyes when exposed to direct sunlight. These findings are expected to provide a useful reference for breeders at Gecko World in optimizing husbandry practices and improving animal welfare by considering the unique characteristics and behavioral responses of each morph.